The stereospecificity of flobufen metabolism in isolated guinea pig hepatocytes - Kral, Radim; Skalova, Lenka; Szotakova, Barbora; Velik, Jakub; Schroterova, Ladislava; Babu, Yogeeta N; Wsol, Vladimir (BMC pharmacology, 2003)
BACKGROUND: Flobufen (F) is an original nonsteroidal anti-inflammatory drug with one center of chirality. 4-Dihydroflobufen (DHF), compound with two chiral centers, is the main metabolite of F in microsomes and cytosol in all standard laboratory animals. This work describes the biotransformation of F enantiomers and DHF stereoisomers in isolated male guinea pig hepatocytes. Guinea pigs were chosen with respect to similarities in F metabolism as in Man found earlier. R-F, S-F, (2R;4S)-DHF, (2S;4R)-DHF, (2S;4S)-DHF and (2R;4R)-DHF, structurally very similar compounds, served as substrates in order to observe their interaction with enzymes. Stereospecificity of the respective enzymes was studied in vitro, using hepatocytes monolayer. Chiral HPLC using R,R-ULMO column as chiral stationary phase was used for detection and quantitation of metabolites. RESULTS: (2R;4S)-DHF and (2S;4S)-DHF were the principle stereoisomers detected after incubation with rac-F, R-F and S-F. The ratio of (2R;4S)-DHF/(2S;4S)-DHF ranged from 1.1 to 2.4 depending on the substrate used. (2R;4S)-DHF was the major stereoisomer found after incubation with (2S;4S)-DHF and (2R;4R)-DHF. (2S;4S)-DHF was the principle stereoisomer found after incubation with (2R;4S)-DHF and (2S;4R)-DHF. Besides DHF stereoisomers, other metabolites (M-17203, UM-1 and UM-2) were also detected after incubation of hepatocytes monolayer with F. Interestingly, these metabolites were not found in incubation of all F forms and DHF with fresh liver homogenate. CONCLUSIONS: Different activities and stereospecificities of the respective enzymes were observed for each substrate in primary culture of hepatocytes. Cell integrity is crucial for formation of secondary metabolites M-17203, UM-1 and UM-2.
Keywords: butyráty; antiflogistika; Animals; Guinea Pigs; In Vitro Techniques; Hepatocytes; Butyrates; Male; Stereoisomerism; techniky in vitro; mužské pohlaví; Anti-Inflammatory Agents; vysokoúčinná kapalinová chromatografie; morčata; Chromatography, High Pressure Liquid; zvířata; stereoizomerie; hepatocyty